A Novel Potentiometric PVC-membrane Cysteamine-Selective Electrode Based on Cysteamine-Phosphomolybdate Ion-Pair - Tumur, Merve; Kanberoglu, Gulsah S.; Coldur, Fatih (Current Pharmaceutical Analysis, 2020)
Background: Cysteamine is used as an orphan drug in the treatment of cystinosis to prevent long-term cystine accumulation in lysosomes. Dosing in cysteamine treatment is extremely important and overdose may cause some side effects. Up to now, various analytical methods have been used for cysteamine determination. Many of these methods require sophisticated instruments, expert operators, time-consuming measurement procedures and manipulation steps, expensive supplies and long analysis time. Aims and Objective: The present study deals with the development of a potentiometric PVC-membrane cysteamine-selective electrode based on an ion-pair of cysteamine and its application in a pharmaceutical formulation. Methods: Cysteamine (Cys)-Phosphomolybdate (PM) ion-pair was synthesized by mixing the equal volumes of 10-2 M Cysteamine HCl and sodium phosphomolybdate aqueous solutions. The obtained precipitate was used as ionophore in the structure of PVC-membrane. Results and Discussion: The electrode exhibited a linear response in the concentration range of 1.0x10- 1-1.0x10-5 M cysteamine with a slope of 51,7 mV per decade and detection limit of 1.0x10-5 M. The potentiometric response of the electrode was very rapid (5 s), adequately repeatable, stable and selective. pH working range and life-time of the electrode were also determined as 3.0-7.0 and 25 days, respectively. Conclusion: A PVC-membrane cysteamine selective electrode was easily prepared. Cysteamine determination in a pharmaceutical formulation was performed. Analysis results indicated that it can be successfully used in drug quality control laboratories for routine analysis of cysteamine in pharmaceutical preparations alternative to more sophisticated, expensive and time-consuming analytical methods.
Keywords: cysteamine determination